Cover Picture: Interaction of dendrimers with the immune system: An insight into cancer nanotheranostics (View 3/2021). Issue 3 (17th June 2021) - Gao, Yue; Shen, Mingwu; Shi, Xiangyang
Abstract : In article number 20200120, Xiangyang Shi, Mingwu Shen and a co‐worker review the immunomodulatory effects of certain types of dendrimers, the recent advances in dendrimer‐facilitated cancer immunotherapy and immunity visualization, and clarify the possible future perspectives for the design of dendrimer‐based cancer immunotheranostics.